The Impact of Instagram Endorsement on Consumer Buying Interest in Indonesian Local Cosmetic Product - Intan Sumita Ino; Linda Dwi Putri Juniawan (Budapest International Research and Critics University, 2022)
The current era of technology makes Smartphones bring new changes in social activities. People are starting to use gadgets with the internet and cell phones being an essential item to carry. In fact, many people use two phones at the same time. In particular, gadgets or smartphones have ruled the world in the last ten years. Indonesia is one of the countries that is also affected by technological developments. Smartphones have brought a new way of doing social activities. It's related to